Persian Rumi in American context : investigating ideological manipulation of illustrations - Naghmeh-Abbaspour, Bita; Amini, Mansour (Penerbit Universiti Kebangsaan Malaysia, 2022)
Images are never innocent and are always constructed through different practices and ideologies. This fact is true for book illustrations and becomes still more complicated if the illustrations have been created for a literary translated text. This paper analysed the visual signs of ideologies in ten frames of illustration accompanied an English translation of Rumi’s poetry to examine the ideological congruency of these illustrations with the worldview of the original text. Considering ‘discourse’ in Foucauldian sense, that pictures and images can be understood as discourse, and based on the constant association of discourse and ideology, the present study employed discourse analysis as its analytical tool. Therefore, to accomplish its objective, this study investigated the ideological contents of the collected illustrations. The findings demonstrated that the illustrations present a totally diverse ideology compared to that of the original text. The current research has implications for the young translating practitioners and researchers to be aware of the pitfall of ideological manipulation through illustrations.